Identification of an immunodominant antigenically conserved 32-kilodalton protein from Cowdria ruminantium. - Jongejan, F (1989)
Western blotting (immunoblotting) of Cowdria ruminantium antigens with goat or mouse antiserum identified a periodate-resistant, proteinase K-sensitive immunodominant antigen of 32,000 daltons. This protein, designated Cr32, could be demonstrated in goat choroid plexus infected with one of two different Cowdria stocks. Antisera against nine different Cowdria stocks from Africa and the Caribbean region recognized Cr32, which indicates that this protein contains conserved antigenic determinants.